Rethinking the East Asian developmental state in its historical context: finance, geopolitics and bureaucracy. Issue 1 (2nd January 2017) - Yeung, Henry Wai-chung
ABSTRACT: This paper critically revisits the statist literature that stresses the central role of the developmental state in steering economic development in East Asia. Based on a critique of the existing literature on the state's mobilization of financial resources and implementation of industrial policy between the late 1950s and the 1980s, it argues that East Asian industrial transformation must be situated in the peculiar historical contexts of favourable geopolitical imperatives and contested domestic bureaucratic rationality. This rethinking is useful because more developing countries are now following the kind of top-down state governance and interventionist policies pursued previously by these East Asian developmental states. And yet they might not give careful considerations to these important historical specificities underpinning the success or failure of such developmentalist policies.